Pola Emosi Tokoh Gia dalam Novelet Si Timu Karya Ai Koraliati: Kajian Psikologi Sastra - Syarifah, Syarifah; Karlina, Kiki; Koswara, Dedi; Darajat, Danan (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to describe emotional patterns using Elizabeth B. Hurlock's theory found in Ai Koraliati's novella Si Timu. This novella tells the story of a family that keeps a cat. This study uses a qualitative descriptive approach. The data source in this study is the novella Si Timu by Ai Koraliati. The data collected in this study are words and sentences found in the novella. The results of the structural analysis include (1) the theme, which is a family that loves animals, (2) the main characters, which are Gia and additional characters Agi, Angga, Gia's parents, Eroh, Ikal, and Bapa Ikal. (3) the plot used is a forward plot (4) the setting is divided into two, including the place and time settings (5) the point of view used is the omniscient third person. The results of the analysis of the eight emotional patterns found 27 data fragments; 4 anger, 2 fear, 2 jealousy, 3 curiosity, 5 envy, 4 joy, 4 sadness, and 3 affection.